From easter eggs to anti-police sentiment: Maintaining a balance in policing during the three pandemic lockdowns in England and Wales - Jenny Fleming; Jennifer Brown (Administrative Sciences, 2023)
The three lockdown periods across 2020-2021 due to COVID-19 had significant consequences for police. Pandemic lockdown experiences were explored based on online interviews with 25 officers of varied ranks and from across five regions in England and Wales. The analysis demonstrates the existence of two counter-prevailing dynamics in the working world of police in England and Wales across the three lockdown periods. Changing government directives, deteriorating relationships between the police and the public and senior officers' sensitivity to the needs of the workforce, were foci of concern and discussion. On reflection, officers acknowledged that relationships between senior management and police improved over the three lockdowns. However, officers found it difficult to balance the demands of the profession and the claims of the state while seeking to retain policing by consent with an increasingly fractious public unsettled by restrictions to their freedom of movement and government activity.
Keywords: 350; COVID-19; pandemic; policing; procedural justice; serving leadership